2013
DOI: 10.4161/gmcr.24324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth hormones on some antioxidant parameters and gene expression in tomato

Abstract: Bioregulators have a great effect on vital processes of plant growth and development. Known plant bioregulators include Naphthalene acetic acid (NAA), Indole-3-butyric acid (IBA) and Indole-3-acetic acid (IAA). Natural or synthetic plant bioregulators are organic compounds that affect the physiological processes in the plant, either to control some of these processes or to modify them. For example these bioregulators can affect the nature of the process, either by accelerating or decelerating plant growth, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Antioxidants are mostly expressed to cope with stressed situations and their expression also has positive effects on the activation of enzymes related to plant growth [58,59]. In the present study, plant-derived smoke is behaving as a growth promoter and thus did not affected ascorbate peroxidase enzyme levels (Figure 7A).…”
Section: Discussionmentioning
confidence: 47%
“…Antioxidants are mostly expressed to cope with stressed situations and their expression also has positive effects on the activation of enzymes related to plant growth [58,59]. In the present study, plant-derived smoke is behaving as a growth promoter and thus did not affected ascorbate peroxidase enzyme levels (Figure 7A).…”
Section: Discussionmentioning
confidence: 47%
“…Sucrose is one of the compatible solutes that get accumulated in plants, particularly under drought or salt stress [9]. In this study, treatment of plants with NaCl led to the highest increase in sucrose (3.2x).…”
Section: Discussionmentioning
confidence: 62%
“…Global production of tomato was estimated at over 153 million metric tonnes in 2009 [8]. Tomato consumption has been linked to reduced risks of cancer especially prostate cancer and reduced occurrence of cardiovascular diseases [9]. This is because tomato contains high amounts of antioxidants such as vitamins A, C and E, carotenoids, flavonoids and phenolic acids [10].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the concentration of SA, the concentration of total phenolic compounds and total flavonoids was improved, obtaining the highest concentration of these compounds at a dose of 0.5 mM, exceeding the control treatment by 37.5% and 45.46%, respectively. El-Gaied et al (2013) observed that phytochemical compounds are increased in response to a biochemical stress in cell suspensions caused by the increase in SA [27]. It has also been found that SA induces the production of hydrogen peroxide (H 2 O 2 ), which stimulates a greater activity of phenylalanine ammonium lyase, responsible for the synthesis of phenolic compounds [28].…”
Section: Discussionmentioning
confidence: 99%